PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM TERHADAPBELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2004-2007 - Andriana Andriana (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2012)
This research intends to empirically test the direct effect between Regional Real/Own Revenue (PAD) and General Allocation Fund (DAU) towards Capital Expenses at the Regency/Municipality of Central Java Province. Sample in this research is overall Regencies and Municipalities located in Central Java from the year of 2004 to 2007. The sample used based on the Regional Revenue and Expense Budget (APBD) of regency/municipality regional government that had been used the new format that is Law of the Internal Affairs Minister Decree No. 29 year 2002. Data analyzed by using multiple regressions technique with analysis path model and e-views. Based on the research result using multiple regressions, gained the first Hypothesis result that is Regional Real/Own Revenue negatively affects Capital Expenses. Second Hypothesis shows that General Allocation Fund positively affects Capital Expenses. Keyword: Regional Real/Own Revenue (PAD), General Allocation Fund (DAU), Capital Expenses.